Hubungan Minat Ibu, Dukungan Suami, dan Pelayanan KB terhadap Pemilihan Alat Kontrasepsi dalam Rahim (AKDR) di Rumah Sakit Nuraida - Shintya, Yona; Idealistiana, Lia (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The use of Long-Term Contraceptive Methods (LCM), especially IUDs, has not been the main choice. In 2023, the prevalence of active IUD users in Nuraida Hospital was still low at 8.3%. Several factors that do not support the use of IUD contraceptive methods include maternal interest, husband's support, and family planning services. To determine the relationship between maternal interest, husband's support, and family planning services on the choice of Intrauterine Contraceptive Devices (IUDs) at Nuraida Hospital. This study is a quantitative analytical study with a cross-sectional design. . The sample in the study was 31 women of childbearing age with a purposive sampling technique. The research instrument used a questionnaire. The data is primary data analyzed using a square test. The results of the univariate analysis showed that most did not choose Intrauterine Contraceptive Devices (IUDs) 64.5%, with moderate maternal interest 54.8%, negative husband's role 61.3% and family planning services not available 58.1%. The results of the bivariate analysis showed that there was a significant relationship between interest (p value = 0.007), husband's role (p value = 0.007), and family planning services (p value = 0.021) with the selection of IUDs. There is a relationship between interest, husband's role and family planning services with the selection of IUDs.  Keywords: Interest, Husband's Role, Family Planning Services, Selection of IUDs  ABSTRAK Pengunaan Metode Kontrasepsi Jangka Panjang (MKJP) khususnya AKDR belum menjadi pilihan utama. Rumah Sakit Nuraida tahun 2023 prevalensi KB aktif pengguna AKDR masih rendah sebanyak 8,3%. Beberapa faktor yang kurang mendukung menggunakan metode kontrasepsi AKDR diantaranya minat ibu, dukungan suami dan pelayanan KB.Mengetahui hubungan minat ibu, dukungan suami, dan pelayanan kb terhadap pemilihan Alat Kontrasepsi Dalam Rahim (AKDR) di Rumah Sakit Nuraida. Penelitian ini merupakan penelitian analitik kuantitatif dengan rancangan cross sectional. . Sampel dalam penelitian adalah wanita usia subur sebanyak 31 responden dengan teknik purposive sampling. Instrumen penelitian menggunakan kuesioner. Data merupakan data primer dianalisis menggunakan uji uji  square. Hasil analisis univariat diketahui sebagian besar tidak memilih Alat Kontrasepsi Dalam Rahim (AKDR) 64,5%,dengan minat ibu sedang 54,8%, peran suami negatif 61,3% dan pelayanan KB tidak tersedia 58,1%. Hasil analisis bivariat diketahui bahwa ada hubungan yang signifikan antara minat (p value = 0,007), peran suami (p value = 0,007), dan pelayanan KB (p value = 0,021) dengan pemilihan AKDR. ada hubungan antara minat, peran suami dan pelayanan KB dengan pemilihan AKDR. Kata Kunci: Minat, Peran Suami, Pelayanan KB, Pemilihan AKDR